Peran Pemerintah Daerah Kabupaten Sambas dalam Pengembangan Ekonomi kawasan Wisata Bukit Piantus Berbasis Wisata Halal - Eka Feriyanto (CV. KAMPUS AKADEMIK PUBLISING, 2024)
. This research aims to find out the role of the government in developing the economy of the Bukit Piantus tourist area based on halal tourism. This type of research uses a qualitative approach by producing descriptive data. Research data was collected using the interview method of 5 informants. Data analysis includes data collection, data reduction, data classification, data display, conclusions and verification. The results of research regarding the Role of the Sambas Regency Regional Government in the Economic Development of the Piantus Hill Tourism Area show that the Government's role as a Motivator is by providing synergy between the Government and the Community and the Private Sector, while the Government's Role as a Facilitator is by providing skills development assistance to the people of Piantus Village and the Regency Government is carrying out procurement and development of facilities at Piantus Hill Tourism, the role of the Government as a dynamist in synergy with the community and the private sector in developing Piantus Hill Tourism so that it can develop the economy of the community in the Piantus Hill area, supporting factors in the economic development of the Piantus Hill Tourism area are the participation of the Piantus Village community and having The potential of this tourist attraction can be an attraction for tourists, but inhibiting factors such as limited budget for facilities and infrastructure costs and land problems in the Bukit Piantus tourist area can slow down the development of Bukit Piantus tourism.